Choices for school leavers [Sound recording] : case studies from the real world - Leigh, Richard , 1943-2007 (Bendigo, Victoria : Video Education Australasia, 2004)
Throughout secondary school, students are repeatedly asked to make decisions relating to career paths. These times can be very stressful for both students and parents as they try to weave their way through the maze of options strewn in their paths. In this program, young people who have already made the school to work transition offer invaluable insight to students who are searching for a career path
Camera, Richard Leigh; Sound, Wayne Martin; Editor, Paul Sutherland; DVD editor, Greg Laugher; Production manager, Edwina Baden-Powell; Educational consultant, Julie Ryan; ChrWriter/producer/director, Richard Leigh; Commissioning editor, Christine Henderson; Executive producer, Mark Mcauliffe
Voiceover, Mark Colland; With thanks, Heather Crosling, Megan Dunn, Lara Cameron, Louise Iozzi, Aaron Mcgowan, Joanne Wood, Chris Walkley, Allan Montague, Meagan Reay, Julie Ryan, Michael, Laura, Kylie, Luke, Gillian Farrel, Suzzanne Barrah, Wayne, Sarah, Chris, Evelyn, Giullo
Keywords: Career development; Vocational guidance